Digitizing Darul Faqih Islamic boarding school in Indonesia: Teachers' perspectives on hybrid Islamic boarding school - Hanafi, Yusuf; Ikhsan, M. Alifudin; Saefi, Muhammad; Diyana, Tsania Nur; Anam, Faris Khoirul; Ramadhan, Mochammad Rizal (PERDIKAN (Journal of Community Engagement), 2025)
The COVID-19 pandemic has impacted the closure of almost all learning processes in Islamic boarding schools. Only some Islamic boarding schools have succeeded in modifying learning methods, one of which is the Darul Faqih Indonesian Islamic Boarding School located in Malang Regency, Indonesia. This community service aims to support efforts to strengthen the digitalisation of Darul Faqih Indonesian Islamic boarding school and direct the development of hybrid Islamic boarding schools after the Covid-19 pandemic. This community service activity consists of two phases. First, at the beginning of the semester, teachers are given training to strengthen the use of learning management systems and mobile apps. In the second phase, the teacher was invited back to conduct a focus group discussion at the end of the implementation. At the end of this service activity, impact measurements were also carried out from a teacher's perspective. A total of 58 teachers participated in this activity. Less than half of teachers have a preference for mixed learning. However, they have high self-efficacy in implementing effective learning to support the implementation of hybrid pesantren. Constraints during mixed learning are appropriate technological and pedagogical support. Despite some challenges, teachers have so far been able to adapt to various online learning methods. Most agree that blended learning can be next as the next main effort towards hybrid pesantren.[Pandemi Covid-19 berdampak pada penutupan hampir semua proses pembelajaran di pondok pesantren. Hanya sebagian pondok pesantren yang berhasil memodifikasi metode pembelajaran, salah satunya adalah Pondok Pesantren Darul Faqih Indonesia yang berlokasi di Kabupaten Malang, Indonesia. Pengabdian masyarakat ini bertujuan untuk memberikan dukungan dalam upaya penguatan digitalisasi pesantren Darul Faqih Indonesia dan mengarahkan pada pembangunan pesantren hibrid pasca pandemi Covid-19. Kegiatan pengabdian masyarakat ini terdiri dari dua fase. Pertama, pada awal semester, guru diberikan pelatihan untuk penguatan penggunaan learning manajemen system dan mobile app. Fase kedua, di akhir penerapan, guru diundang kembali untuk melakukan Focus Group Discussion. Di akhir kegiatan pengabdian ini juga dilakukan pengukuran dampak berupa perspektif guru. Sebanyak 58 guru berpartisipasi dalam kegiatan ini. Kurang dari separuh guru yang memiliki preferensi terhadap pembelajaran campuran. Namun, mereka memiliki efikasi diri yang tinggi dalam melaksanakan pembelajaran yang efektif untuk mendukung implementasi pesantren hibrid. Kendala selama pembelajaran campuran adalah dukungan teknologi dan pedagogi yang tepat dan sesuai. Meskipun ada beberapa tantangan, guru sejauh ini mampu beradaptasi dengan berbagai metode pembelajaran daring, dan mayoritas setuju bahwa pembelajaran campuran dapat diterapkan selanjutnya sebagai upaya utama menuju pesantren hibrid.]